2014
DOI: 10.1089/met.2013.0129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of the Renin–Angiotensin System Blockers on Nonalcoholic Fatty Liver Disease and Insulin Resistance in C57Bl/6 Mice

Abstract: Enalapril was the most successful treatment in protecting against hepatic IR and NAFLD by enhancing hepatic insulin action, leptin, and gluconeogenesis and by reducing the lipogenic pathway and lipid accumulation in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Additionally, this is related to the stimulation of lipogenic enzymes and the inhibition of mitochondrial β‐oxidation, thus contributing to the development of NAFLD (Frantz et al . ). These findings in the HFr group were lessened by exercise training, reverting hepatic steatosis, TAG accumulation and restoring the morphology of the hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, this is related to the stimulation of lipogenic enzymes and the inhibition of mitochondrial β‐oxidation, thus contributing to the development of NAFLD (Frantz et al . ). These findings in the HFr group were lessened by exercise training, reverting hepatic steatosis, TAG accumulation and restoring the morphology of the hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have revealed that RAS imbalance appears to promote hepatic disease, whereas activation of the ACE2/Ang(1–7)/Mas axis is able to prevent it (Frantz et al . ; Cao et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistency of body weight reductions in mice with genetic deficiencies of major renin angiotensin components contrasts with the phenotypes of pharmacological inhibition of these same proteins. A small number of studies using renin, ACE, or AT1 receptor inhibition have reported modest reductions in saturated fat diet induced body weight gain in mice, 38-44 while the vast majority of studies using pharmacological inhibition of renin, ACE, or AT1 receptors in mice fed a saturated fat diet have failed to observe any effect on body weight (more than 60 papers including 8,12,40,45-47 ). These data from mice is consistent with no data implicating body weight changes in humans treated with renin angiotensin system pharmacological inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the involvement of AGT II in NAFLD pathogenesis and in atherosclerotic plaque formation may provide one of the possible links between NAFLD and accelerated atherogenesis. Accordingly, the use of RAS blockers seems to be potentially useful as a therapeutic approach against NAFLD [12] and atherosclerosis [13]. To date, there is no single approved pharmacologic therapy to treat metabolic dysfunctions occurring in obesity, such as NAFLD and related atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%